Remarks on the Spin-One Duffin-Kemmer-Petiau Equation in the Presence of Nonminimal Vector Interactions in (3+1) Dimensions. (19th June 2014) - Castro, L. B.; de Oliveira, L. P.
Abstract : We point out a misleading treatment in the recent literature regarding analytical solutions for nonminimal vector interaction for spin-one particles in the context of the Duffin-Kemmer-Petiau (DKP) formalism. In those papers, the authors use improperly the nonminimal vector interaction endangering in their main conclusions. We present a few properties of the nonminimal vector interactions and also present the correct equations to this problem. We show that the solution can be easily found by solving Schrödinger-like equations. As an application of this procedure, we consider spin-one particles in presence of a nonminimal vector linear potential.